Performance of apricot (Prunus armeniaca) genotypes for growth, yield and quality parameters in temperate ecosystem of Himachal Pradesh - SHUKLA, A K; PRAMANICK, K K; WATPADE, SANTOSH; KUMAR, J (The Indian Journal of Agricultural Sciences, 2018)
Studies were carried out to assess the performance of fifteen apricot (Prunus armeniaca L.) genotypes for growth, yield and quality characters in temperate region of Himachal Pradesh. Based on observations during 2013 to 2016 at ICAR-Indian Agricultural Research Institute, Regional Station, Shimla tree height varied from 2.16-5.75 m, tree girth varied from 30.5-98.5 cm with maximum in Charmagaz (98.5 cm) and minimum in Nugget (30.5 cm). Canopy spread in East-West direction varied from 2.13-7.0 m with the maximum in Charmagaz (7.0m) and minimum in Harcot (2.13m). Canopy spread in North-South direction was also maximum in Charmagaz (6.80m). Plant dormancy varies from 129-154 days in different genotypes of apricot. Highest fruit set was recorded in EC-168342 (46.32%) and minimum found in Harcot (11.78%). The fruit weight was maximum in EC-168342 (86.56 g) and minimum in Nugget (20.07 g). Pulp weight was also recorded maximum in EC-168342 (82.44 g) and minimum in Nugget (17.74g). Fruit size (LÃ—B) was highest in EC-168342 (5.39 cm Ã— 5.16 cm). The stone weight in different genotypes varied from 2.33-4.52g with maximum in EC-232328 (4.52g) and minimum in Nugget (2.33g). Fruit yield varied from 5.31-26.13 t/ha with maximum in EC-168342 (26.13 t/ha) and minimum in Nugget (5.31 t/ha). Dry matter content varied from 18.01%- 26.66% with maximum in New Castle (26.66%). Pulp thickness was recorded maximum in Suffaida Oblonga (12.2 mm) and minimum observed in New Castle (6.32 mm). Total soluble solids (TSS) was recorded maximum in Charmagaz (18.31%) and minimum in Harcot (12.83%). Acidity in fruit was recorded highest in EC-168342 (2.01%) and minimum in Nari Kinnaur (0.98%). The highest reducing sugar was observed in Nari Kinnaur (7.21%) with minimum was recorded in EC-232328 (3.16%). Non-reducing sugar varied from 4.52%-9.24% with maximum in Castle (9.24%). Vitamin-C content was significantly higher in EC-168342 (17.16 mg/100 g) and minimum in Shipley Early (11.98 mg/100 g).